APPLICATION OF EDUCATIONAL TECHNOLOGIES IN IMPROVING PROFESSIONAL AND METHODOLOGICAL TRAINING OF FUTURE FINE ARTS TEACHERS (CAHIERS MAGELLANES-NS, 2024)
The article reveals the essence of the pedagogical conditions for the development of professional and methodological training of future fine arts teachers using educational technologies. Also covered are the issues of developing professional and methodological skills using educational technologies for painting and composition classes, as well as an analysis of the research works of teachers and scientists dealing with the problem of professional and methodological training of students,